Antibody persistence and immune memory 4 years post-vaccination with combined hepatitis A and B vaccine in adults aged over 40 years - Chlibek, Roman; von Sonnenburg, Frank; Van Damme, Pierre; Smetana, Jan; Tichy, Petr; Gunapalaiah, Bhavyashree; Leyssen, Maarten; Jacquet, Jeanne-Marie (Journal of travel medicine, 2011)
Persistence of immune response was assessed in adults aged >40 years (N = 596) following primary vaccination with combined hepatitis A/B vaccine or concomitant monovalent hepatitis A and B vaccines. Anti-hepatitis A virus antibody responses persisted for at least 4 years regardless of the vaccine used, with anti-hepatitis B surface antibody responses higher and more sustained in subjects who received the combined hepatitis A/B vaccine. Response rates to an additional dose of the same vaccine(s) used for priming were high.
Keywords: Hepatitis A; dospělí; Vaccines, Combined; sekundární imunizace; Female; Hepatitis B; Adult; ženské pohlaví; Hepatitis B Vaccines; hepatitida B; kombinované vakcíny; lidé; vakcína proti hepatitidě A; hepatitida A - protilátky; Male; hepatitida A; vakcína proti hepatitidě B; imunologická paměť; lidé středního věku; Hepatitis B Antibodies; mužské pohlaví; Hepatitis A Vaccines; Immunization, Secondary; Hepatitis A Antibodies; Middle Aged; hepatitida B - protilátky; Immunologic Memory; Humans